Massive lower gastrointestinal bleeding from idiopathic ileocolonic varix: report of a case - LOPES, L.M. (2006)
Dis Colon Rectum. 2006 Apr;49(4):524-6. Massive lower gastrointestinal bleeding from idiopathic ileocolonic varix: report of a case. Lopes LM, Ramada JM, Certo MG, Pereira PR, Soares JM, Ribeiro M, Areias J, Pinho C. SourceGastroenterology Department, Hospital Geral Santo António, Porto, Portugal. Luis.m.lopes@sapo.pt Abstract Idiopathic varices of the entire colon are very rare. We report on a 64-year-old patient with massive lower gastrointestinal hemorrhage from an extensive ileocolonic varix. Diagnosis was established by colonoscopy. The patient underwent an emergency ileocolectomy with satisfactory results. This rare case shows the importance of colonoscopy in the evaluation of patients with lower gastrointestinal hemorrhage and reminds us that sometimes the diagnosis is not what we expect. Recognition of this abnormality is important because varices may be the cause of massive lower gastrointestinal hemorrhage. PMID: 16395635 [PubMed - indexed for MEDLINE]